The Origin of German Tragic Drama - Benjamin, Walter 1892-1940 (London Verso, 1998)
The Origin of German Tragic Drama is Walter Benjamins most sustained and original work. It begins with a general theoretical introduction on the nature of the baroque art of the sixteenth and seventeenth centuries, concentrating on the peculiar stage-form of royal martyr dramas called Trauerspiel. Benjamin also comments on the engravings of Dürer and the theatre of Calderon and Shakespeare. Baroque tragedy, he argues, was distinguished from classical tragedy by its shift from myth into history. Georg Lukacs, an opponent of Benjamins aesthetics, singled out The Origin of German Tragic Drama as one of the main sources of literary modernism in the twentieth century.
Keywords: 16th Century (1501-1600); 17th Century (1601-1700); Theater history; Baroque; Germany